Steamer DOLPHIN under service to Alaska Steamship Company, between 1900 and 1917 - University of Washington Libraries. Special Collections (1900)
Caption on postcard: The A.S.S. Cos. Flyer - Str. Dolphin Filed in: Ships - D Steamer Dolphin was built in 1892 for East Coast service before the Alaska Steamship Company acquired her in 1900. In 1909, she won the speed title in the service from the Steamer City of Seattle, which had held the time and the names "Alaska Flyer" or "Alaska Express" for many years. In 1917, she was sold to South American owners to service the Chilean Coast. The Chilean government later acquired her for use as a gunboat. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number